2015
DOI: 10.1097/rli.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Shift and Diffusion-Weighted Magnetic Resonance Imaging of Thymus in Myasthenia Gravis

Abstract: CS-MRI and DW-MRI are both useful tools for examining patients with MG. The SII is more accurate than the ADC to differentiate TLH and NT from THY (AUROC, 1.000 and 0.931, respectively). Furthermore, the ADC is a noninvasive parameter that could be used for distinguishing TLH from NT, which is useful in selecting patients for surgery because, for nonthymomatous MG, acceptable rates of complete stable remission after thymectomy are found in TLH but not in NT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were reported by Ohno et al, who found better performance of ADC compared to maximum standardized uptake value obtained from PET‐CT as a quantitative predictor of tumor treatment response after chemoradiotherapy in nonsmall‐cell lung cancer . However, the aim of our study was to assess the repeatability of different protocols of ADC measurement that are generally used in other organs and compartments . Thus, the best method of ADC measurement for clinical application in DW‐MRI of the pleura and its benefit in evaluating and predicting treatment response are yet to be determined by means of further studies.…”
Section: Discussionsupporting
confidence: 71%
“…DW‐MRI provides quantitative data that are generally obtained, in the clinical setting, through the measurement of the apparent diffusion coefficient (ADC) . Several studies have shown the ability of quantitative DW‐MRI to characterize benign and malignant disease in different organs and compartments . However, several factors, which include also the manual method of region‐of‐interest (ROI) positioning for measuring the ADC, affect the measurement and can lead to unreliable values .…”
mentioning
confidence: 99%
“…Moreover, MRI enable the correct diagnosis in one case of triangular-shaped THY, which was interpreted as a diffusely enlarged thymus with soft-tissue attenuation at CT. 11 Such high reliability of chemical-shift MRI in detecting fat in tissue is similar to that of previous studies that evaluated normal/hyperplastic thymus and anterior mediastinal tumours in mixed pop-ulations of different diseases. 11,12,16,17,31,32 Nevertheless, visual assessment of signal intensity loss at chemicalshift MRI for characterising NT and TLH has limitations because its inability to detect fat in NT of adolescents and children <16 years (two cases in the present cohort) and in sporadic cases of adults with NT, TLH, or rebound hyperplasia previously reported in literature. 12,18,31,33,34 One case of partially non-suppressing TLH occurred in a 71-year-old woman because of extensive areas of lymphoid follicles with no fatty infil-tration at histology.…”
Section: Qualitative Assessmentmentioning
confidence: 80%
“…In such cases, diffusion-weighted imaging may be helpful by demonstrating unrestricted diffusion in a normal or hyperplastic thymus. 17,34 Indeed, because diffusion-weighted imaging provides information related to the cell density and cellular architecture of tissues based on the random translational molecular motion of water molecules, it has been used in different organs for distinguishing benign from malignant lesions through the measurement of the apparent diffusion coefficient (ADC), which is significantly lower in malignant tumours (e.g., high-grade THY and mediastinal lymphoma) compared with normal tissues or hyperplastic thymus (e.g., NT and TLH, which do not suppress on opposed-phase imaging because of the low lipid content within the thymus, as generally seen in young patients Quantitative analysis: unenhanced and contrast-enhanced CT For unenhanced and contrast-enhanced CT, no difference was found in the attenuation of the NT compared with TLH. Conversely, in their cohort of 15 patients, Araki et al 45 re-ported higher attenuation of the thymus in the TLH group compared with the true hyperplasia group (a condition indistinguishable from NT at histology) at contrast-enhanced CT, although these data were not confirmed at unenhanced CT.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
See 1 more Smart Citation